The Effect of Zakat Transparency and Government Support on Public Trust and Poverty Alleviation in West Java - Ahmad Ari Mansyuri; KMT Lasmiatun; Dedi Mardianto; Ariyadi Ariyadi (West Science Social and Humanities Studies, 2025)
This study examines the effects of zakat transparency and government support on community trust and poverty alleviation in West Java. Using a quantitative approach, data were collected from 120 respondents through a structured questionnaire employing a Likert scale (1-5). The data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS 3). The results reveal that both zakat transparency and government support positively influence community trust, which acts as a mediator between zakat transparency, government support, and poverty alleviation. The findings indicate that when zakat institutions are transparent and the government provides adequate support, community trust is fostered, leading to more effective poverty alleviation efforts. This study underscores the importance of transparency and government involvement in poverty reduction programs, offering valuable implications for policymakers and zakat institutions.